Quantitative Measure to Differentiate Wicket Spike from Interictal Epileptiform Discharges - Suryani Gunadharma; Ahmad Rizal; Rovina Ruslami; Tri Hanggono Achmad; See Siew Ju; Juni Wijayanti Puspita; Sapto Wahyu Indratno; Edy Soewono (Indonesian Bio-Mathematical Society, 2021)
A number of benign EEG patterns are often misinterpreted as interictal epileptiform discharges (IEDs) because of their epileptiform appearances, one of them is wicket spike. Differentiating wicket spike from IEDs may help in preventing epilepsy misdiagnosis. The temporal location of IEDs and wicket spike were chosen from 143 EEG recordings. Amplitude, duration and angles were measured from the wave triangles and were used as the variables. In this study, linear discriminant analysis is used to create the formula to differentiate wicket spike from IEDs consisting spike and sharp waves. We obtained a formula with excellent accuracy. This study emphasizes the need for objective criteria to distinguish wicket spike from IEDs to avoid misreading of the EEG and misdiagnosis of epilepsy.